2004
DOI: 10.1200/jco.2004.04.128
|View full text |Cite
|
Sign up to set email alerts
|

Short-Term Efficacy of Methylphenidate: A Randomized, Double-Blind, Placebo-Controlled Trial Among Survivors of Childhood Cancer

Abstract: Treatment with MPH can at least temporarily reduce some attentional and social deficits among survivors of childhood ALL and BT. Long-term follow-up will reveal those subsets of patients who are more likely to benefit from MPH.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
91
0
2

Year Published

2007
2007
2013
2013

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 172 publications
(94 citation statements)
references
References 27 publications
1
91
0
2
Order By: Relevance
“…More specifically, they identified improved vigilance in attention and caregiver reports of more efficacious everyday attention/concentration as major benefits of treatment. Mulhern et al [2004a] published a subsequent study that is similarly rigorous. Again, the population was longterm survivors of ALL and brain tumors; 83 individuals were enrolled.…”
Section: Pharmacological Interventions For Survivors Of a Pediatric Cmentioning
confidence: 87%
“…More specifically, they identified improved vigilance in attention and caregiver reports of more efficacious everyday attention/concentration as major benefits of treatment. Mulhern et al [2004a] published a subsequent study that is similarly rigorous. Again, the population was longterm survivors of ALL and brain tumors; 83 individuals were enrolled.…”
Section: Pharmacological Interventions For Survivors Of a Pediatric Cmentioning
confidence: 87%
“…However, there are several long-term debilitating effects following radiotherapy in children, including cognitive decline and motor, hormonal and psychological-emotional dysfunctions. 4,5 Furthermore, survivors of childhood cancer have an increased risk of long-term cerebrovascular mortality, and the risk of death from cerebrovascular disease increases linearly with the local radiation dose to the prepontine cistern. 6 More than four centuries ago, it was observed that the vascular and the nervous systems show similar anatomical patterning.…”
Section: Introductionmentioning
confidence: 99%
“…Health care resource utilization can be optimized through risk-adapted interventions [Ris, 2007] guided by biopsychosocial staging methods [Kazak et al, 2007] adapted to pediatric brain tumors. Although more research is needed, this approach promises to significantly improve the outcomes of these children by taking advantage of recent evidence showing the importance of contextual factors [e.g., family health and resources; Carlson-Green et al, 1995] in outcomes, and also the mitigating effects of early cognitivebehavioral [e.g., attention training; Butler and Copland, 2002] and pharmacological [Mulhern et al, 2004] interventions. n…”
Section: Future Directionsmentioning
confidence: 98%